PENTINGNYA MOTIVASI KERJA, SUPERVISI KEPALA SEKOLAH, DAN KEPUASAN KERJA DALAM MENINGKATKAN KOMITMEN ORGANISASI GURU [THE INFLUENCE OF JOB MOTIVATION, PRINCIPAL SUPERVISION, AND JOB SATISFACTION ON TEACHERS' ORGANIZATION COMMITMENT] - Seri Kurnia Situkkir (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2021)
This study aims to analyse the influence of work motivation, principal supervision and job satisfaction on teachers' organization commitment in Secondary XYZ School North Jakarta. The data collection in this study is done using a questionnaire to all teachers. The number of respondents is 53 people. The method used in this research was quantitative research by using path analysis method. This study is using Smart PLS program to evaluate the outer model and inner model. The results showed that work motivation gives positive influence to job satisfaction (0,349) as well as principal supervision with a positive influence to job satisfaction (0,631). Work motivation (0,442) and principal supervision (0,336) have a positive influence on organizational commitment. Job satisfaction has an effect on organizational commitment despite small influence (0,013) but it still creates a positive influence.